Frequent loss of Shiga-like toxin genes in clinical isolates of Escherichia coli upon subcultivation. - Karch, H (1992)
Forty-five consecutive patients with various gastrointestinal disorders were identified as having Shiga-like toxin (SLT)-producing Escherichia coli infections. This was shown by the cytotoxic effect of stool extracts in Vero cell cultures which was neutralizable by antibodies to SLTs and by isolation of E. coli that hybridized with DNA probes complementary to SLT-I and SLT-II sequences. When we tested the same strains for SLT genes after subcultivation, the isolates from 15 patients became negative by colony hybridization and polymerase chain reaction and failed to produce SLTs. The instability of SLT genes warrants direct screening methods for clinical material and the development of new culture methods to prevent the loss of SLT genes.